Historical dataset of major educational reforms in Europe in 1950–1990 - Salonen Laura; Pöyliö Heta (Turku Center for Welfare Research, 2022)
This report presents a comparative data on educational reforms in 25 European countries in 1950–1990. The dataset includes cross–national information about three types of educational reforms; changes in school leaving age, removal of educational dead ends and existence of tuition fees in tertiary education. Data is collected from various sources, such as datasets, reports, national documents and research articles. By providing comparative quality data for macro level events, this dataset contributes to the lack of available measures of educational reforms for social, political and economic research. Open access to adequate measurements for educational policy changes over time in multiple countries enables the application of different research designs and the use of advanced methods of analyses where concrete measurements for educational policies can be included.